Corn and bean cultivars in monoculture and intercropping. I. Yield tests - Carvalho, Hélio Wilson Lemos de (Pesquisa Agropecuaria Brasileira, 2014)
Three corn cultivars and six bean cultivars of different sizes and cycles were evaluated, in monoculture and intercropping, in Poço Verde, semi-arid region of Sergipe State, Brazil, aiming to know cultivars behavior in these planting systems. In the monoculture systems, randomized blocks were utilized, with eight replications for corn (Zea mays L.) and six for bean (Phaseolus vulgaris L.). In the intercropping system, corn and bean cultivars were ranked together, in a 3 x 6 factorial scheme, arranged in randomized blocks with three replications. Correlation coeficient showed that both crops were high (r = 0,9 and 0,9 respectively) in the two systems. Independently of corn and bean cultivars utilized, there was a 52 and 29% reduction on grain production in the intercropping system, in relation to the monoculture systems, for corn and bean respectively. Bean cultivars studied interfered differently on corn cultivars production; also, corn cultivars behaved alike on bean cultivars.